Potential vorticity regimes over East Asia during winter. Issue 3 (6th February 2017) - Huang, Wenyu; Chen, Ruyan; Wang, Bin; Wright, Jonathon S.; Yang, Zifan; Ma, Wenqian
Abstract: Nine potential vorticity (PV) regimes over East Asia are identified by applying a Self‐Organizing Map and Hierarchical Ascendant Classification regime analysis to the daily PV reanalysis fields on the 300 K isentropic surface for December–March 1948–2014. According to the surface temperature anomalies over East Asia, these nine regimes are further classified into three classes, i.e., cold class (three regimes), warm class (four regimes), and neutral class (two regimes). The PV‐based East Asian winter monsoon index (EAWMI) is used to study the relationship between PV distributions and the temperature anomalies. The magnitude of cold (warm) anomalies over the land areas of East Asia increases (decreases) quasi‐linearly with the EAWMI. Regression analysis reveals that cold temperature anomalies preferentially occur when the EAWMI exceeds a threshold at ∼0.2 PVU (where 1 PVU ≡ 10 −6 m 2 K kg −1 s −1 ). PV inversion uncovers the mechanisms behind the relationships between the PV regimes and surface temperature anomalies and reveals that cold (warm) PV regimes are associated with significant warming (cooling) in the upper troposphere and lower stratosphere. On average, cold regimes have longer durations than warm regimes. Interclass transition probabilities are much higher for paths from warm/neutral regimes to cold regimes than for paths from cold regimes to warm/neutral regimes. Besides, intraclass transitions are rare within the warm or neutral regimes. The PV regime analysis provides insight into the causes of severe cold spells over East Asia, with blocking circulation patterns identified as the primary factor in initiating and maintaining these cold spells. Key Points: Wintertime circulation regimes over East Asia are analyzed based on isen‐ tropic potential vorticity fields The response in temperature to variations in potential vorticity distributions is characteristic of a first baroclinic mode While warm and neutral regimes often transit into cold regimes, cold regimes rarely transit into warm or neutral regimes